Chromosome-level genome assembly of black carp Mylopharyngodon piceus using Nanopore and Hi-C technologies - Yuxuan Zhang; Yanwen Shao; Xudong Liu; Liang Zhong; Zhaoyan Zhong; Weiwei Zeng; Jiping Zhang; Wenlong Cai; Runsheng Li (Scientific Data)
Abstract Black carp (Mylopharyngodon piceus) is one of the “four famous domestic fishes” in China and an important economic fish in freshwater aquaculture. A high-quality genome is essential for advancing future biological research and breeding programs for this species. In this study, we aimed to generate a high-quality chromosome-level genome assembly of black carp using Nanopore and Hi-C technologies. The final genome assembly was 848.70 Mb in length, with a contig N50 of 3.37 Mb and a scaffold N50 of 34.13 Mb. The genome was anchored onto 24 chromosomes by Hi-C technology. The BUSCO (Benchmarking Universal Single-Copy Orthologs) completeness score of the genome assembly is 97.6% when compared to the Actinopterygii_odb10 database. In total, 203.54 Mb of repeat sequences and 37,418 protein-coding genes were predicted in the genome assembly. Taken together, our study provides a chromosome-level genome assembly, which can serve as a valuable genetic resource to support further biological studies and breeding efforts of black carp.